Benefit of Simulation-Based Training in Medical Adverse Events Disclosure in Pediatrics. Issue 2 (February 2022) - Aubin, Juliette; Rivolet, Océane; Taunay, Anne-Laure; Ragot, Stéphanie; Ghazali, Daniel Aiham; Oriot, Denis
Abstract : Introduction: Adverse events (AEs) in health care are a public health issue. Although mandatory, error disclosure is experienced by health providers as a difficult task. Methods: In this prospective study, the primary objective was to assess performance in disclosing AEs to simulated parents using a validated scale before and after training among a pediatric residents' population. Secondary objectives were to assess correlation with year of residency, sex, and previous experience and to analyze gain in knowledge (theoretical pretest/posttest scores) and satisfaction. Two evaluation simulations (simulation [SIM] 1 and SIM 2) were scheduled at 3-week interval. In the intervention group, mastery learning was offered after SIM 1 including a didactic approach and a training session using role-playing games. For the control group, the course was carried out after SIM 2. Assessments were performed by 2 independent observers and simulated parents. Results: Forty-nine pediatric residents performed 2 scenarios of AE disclosure in front of simulated parents. In the intervention group, performance scores on SIM 2 (72.36 ± 5.40) were higher than on SIM 1 (65.08 ± 9.89, P = 0.02). In the control group, there was no difference between SIM 1 and SIM 2 ( P = 0.62). The subjective scores from simulated parents showed the same increase on SIM 2 ( P < 0.01). There was no correlation with the residents' previous experience or their residency year. There was an increase in self-confidence ( P = 0.04) for SIM 2. There was also an increase in posttest theoretical scores ( P = 0.02), and residents were satisfied with the training. Conclusions: This study showed the benefits of simulation-based training associated with mastery learning in AE disclosure among pediatric residents. It is important to train residents for these situations to avoid traumatic disclosure generating a loss of confidence of the family regarding physicians and possible lawsuits. Abstract : Supplemental digital content is available in the text.